Noble Bondsmen: Ministerial Marriages in the Archdiocese of Salzburg, 1100–1343 - Freed, John B (Cornell University Press, 1995)
Freed documents the network of marriage practices among ministerials in the archdiocese of Salzburg and in the process reconstructs an important and previously unexplored chapter in the rise of the German principalities.